Microproteins (miPs) – the next big thing - Feller, Stephan (BioMed Central, 2012)
With iPS cells, sncRNAs, chromatin modification regulation and cancer stem cells already cooling off again, i.e. not being guaranteed publications in the 'ultimate' journals anymore, what will be very soon the new red-hot (or super-cool, i.e. anything but lukewarm) 'kid on the block'? We would vote for microproteins.